Toward an Analysis of Fascist Fiction: The Contemptuous Narrator in the Works of Brasillach, Céline and Drieu la Rochelle - Mary Jean Green (Studies in 20th & 21st Century Literature, 1985)
Attempts to analyze the nature of French fascist literature have often foundered on the difficulties of defining fascism as a political ideology and on the apparent heterogeneity of the writers themselves. This paper seeks to discern the traces of political ideology in the fiction of Brasillach, Celine and Drieu la Rochelle, the three principal French fascist novelists of the 1930s, through an examination of the literary techniques used in the works themselves. In this reading, the feature common to the texts is not the expression of a collective enthusiasm often identified with fascism but rather the repeated use of a distanced, even contemptuous, narrative voice. This technique can be related to a recognized feature of fascist ideology, a spirit of social hierarchy and anti-egalitarianism and serves to distinguish these texts written under the sign of fascism from the fiction of the same period inspired by an ideology of the Left.
Keywords: French fascist literature; Facism; political ideology; author; Brasillach; Celine; Drieu la Rochelle; French fascist novelist; 1930; collective; enthusiasm; narrative voice; social hierarchy; anti-egalitarianism; fascist ideology